Pengaruh Kebiasaan Membaca Al-Qur’an Terhadap Hasil Belajar PAI Siswa Kelas X di SMK Mandala Leuwiliang Kabupaten Bogor - Herlina; Raharjo (Jurnal Dirosah Islamiyah, 2024)
The Influence of Al-Qur’an Reading Habits on Islamic Education Learning Outcomes of Class X Students at SMK MANDALA Leuwiliang, Bogor Regency. This research is motivated by the low interest of students to get used to reading the Qur'an at SMK MANDALA From this phenomenon, a desire arises to examine whether there is an effect of the habit of reading the Qur'an on student Islamic education learning outcomes. This research is done at SMK Mandala Leuwiliang, Bogor Regency. The research population is 121 students while the sample is 35 people Technique nonprobability sampling used sampling purposive. This study used the quantitative method with a research instrument using a questionnaire for Al-Qur’an Reading Habits and PTS scores for Student Islamic Education Learning Outcomes. Data were analyzed using the Product Moment Correlation Technique. The research results obtained r count = 0.367 > r table = 0.344. Thus Ho is rejected and Ha is accepted, which means there is an influence of Al-Qur’an Reading Habits on Students' PAI Learning Outcomes. Likewise the significance test with the t test shows t count 2.267 > t table 2.035. This means the influence of the habit of reading the Koran Students' PAI learning outcomes are a significant influence, while the contribution of Al-Qur'an Reading Habits is shown by KD (Coefficient of Determination) = 0.135 which means that Al-Qur'an Reading Habits contribute 13.5% to Results Study PAI Students.